Contemporary women's health issues for today and the future - Kolander, Cheryl A.; Ballard, Danny J.; Chandler, Cynthia K. (New York, NY McGraw-Hill, 2011)
"Contemporary Women's Health provides a balanced, comprehensive understanding of the health issues affecting women. Health information is presented within the context of the social and political forces affecting women of all ages, races, and ethnicities. Prevention, health promotion, and becoming a wise healthcare consumer are emphasized throughout the text, while the impact of lifestyle issues and relationships throughout the lifespan on women's health are also explored."--Book jacket.
Pt. 1. Foundations of Women's Health -- Ch. 1. Introducing Women's Health -- Ch. 2. Becoming a Wise Consumer -- Ch. 3. Developing a Healthy Lifestyle -- Pt. 2. Mental and Emotional Wellness -- Ch. 4. Enhancing Emotional Well-Being -- Ch. 5. Managing the Stress of Life -- Pt. 3. Sexual and Relational Wellness -- Ch. 6. Building Healthy Relationships -- Ch. 7. Exploring Women's Sexuality -- Ch. 8. Designing Your Reproductive Life Plan -- Ch. 9. Preventing Abuse against Women -- Pt. 4. Contemporary Lifestyle and Social Issues -- Ch. 10. Eating Well -- Ch. 11. Keeping Fit -- Ch. 12. Using Alcohol Responsibly -- Ch. 13. Making Wise Decisions about Tobacco, Caffeine, and Drugs -- Pt. 5. Communicable and Chronic Conditions -- Ch. 14. Preventing and Controlling Infectious Diseases -- Ch. 15. Preventing and Controlling Chronic Health Conditions -- Ch. 16. Reducing Your Risk of Cancer.
Includes bibliographical references and index.
Keywords: Women -- Health and hygiene